Treatment of Amyloidosis Associated Factor X Deficiency - Spero, Joel A.; Lewis, Jessica H.; Hasiba, Ute; Ellis, Lawrence D. (Thrombosis and Haemostasis, 1976)
This is the tenth patient in thirteen years to be reported with the findings of an isolated factor X deficiency associated with primary amyloidosis. A favorable response to factor IX concentrate was manifested by temporary clinical and laboratory correction of her diathesis. This mode of treatment, therefore, provides an approach to therapy for bleeding complications in this group of patients who have previously failed to respond to fresh frozen plasma.